The effect of a third-dose BNT162b2 vaccine on anti-SARS-CoV-2 antibody levels in immunosuppressed patients. (May 2022) - Saiag, Esther; Grupper, Ayelet; Avivi, Irit; Elkayam, Ori; Ram, Ron; Herishanu, Yair; Cohen, Yael; Perry, Chava; Furer, Victoria; Katchman, Helena; Rabinowich, Liane; Ben-Yehoyada, Merav; et al.
Abstract: Objectives: The recent surge in coronavirus disease 2019 cases led to the consideration of a booster vaccine in previously vaccinated immunosuppressed individuals. However, the immunogenic effect of a third-dose severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccine in immunosuppressed patients is still unknown. Methods: This was an observational cohort study of 279 previously vaccinated immunosuppressed patients followed at a single tertiary hospital in Israel. Patients were administered a third dose of the Pfizer-BioNTech mRNA vaccine (BNT162b2) between July 14 and July 21, 2021. Levels of IgG antibodies against the spike receptor-binding domain of SARS-CoV-2 were measured 3 to 4 weeks after vaccination. Results: Of the cohort of 279 patients, 124 (44.4%) had haematologic malignancies, 57 (20.4%) had rheumatologic diseases, and 98 (35.1%) were solid organ-transplant recipients. Anti–SARS-CoV-2 antibody levels increased in 74.9% of cases. Across the entire cohort, the median absolute antibody levels (expressed in AU/mL) increased from 7 (interquartile range (IQR), 0.1–69) to 243 (IQR, 2–4749) after the booster dose. The response significantly varied across subgroups: The transplant cohort showed the greatest increase in absolute antibody levels (from 52 (IQR, 7.25–184.5) to 1824 (IQR, 161–9686)), followed by the rheumatology (from 22 (IQR, 1–106) to 1291 (IQR, 6–6231)) and haemato-oncology (from 1 (IQR, 0.1–7) to 7.5 (IQR, 0.1–407.5)) cohorts. The χ 2 test was 8.30 for difference in fold change (p = 0.016). Of the 193 patients who were seronegative at baseline, 76 became seropositive after vaccination, corresponding to a 39.4% (95% CI, 32.8%–46.4%) seroconversion rate. Transplant patients had the highest seroconversion rate (58.3% (95% CI, 44.3%–71.2%)), followed by rheumatology (44.1% (95% CI, 28.9%–60.5%)) and haemato-oncology (29.7% (95% CI, 22%–38.8%); χ 2 = 11.87; p = 0.003) patients. Discussion: A third dose of BNT162b2 is immunogenic in most immunosuppressed individuals, although antibody response may differ based on the type of disease and immunosuppression. The antibody level that correlates with protection is still unknown; thus, future studies are needed to evaluate clinical outcomes.